NAVIGATING ANGELTAX: DEFY AND OPPORTUNITY FOR INDIAN START-UPS - Bangundi, Shantkumar A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is home to the world’s 3rd largest start-up ecosystem and has produced a plethora of successful start-ups in the past decade, including BOAT, PAYTM, and OLA. However, the resurgence of the Angel Tax may hinder current growth and prevent India from reaching its goal of becoming the largest start-up ecosystem in the world by 2030. This paper explores impact of Angel tax on Start up in Indian context. Angel tax, introduced aims to curb tax evasion and money laundering. However, its impact on Indian start-ups has been debated. This paper examines the effects of angel tax on start-up funding, growth, innovation, and job creation in the Indian economy over a period of 4 years.